TEACHING GRAMMAR AT A UNIVERSITY LEVEL - Лопатюк, Наталія; Лукащук, Михайло (ГО «Наукова філологічна організація «ЛОГОС», 2021)
To help students acquire grammatical competence in English, we use explicit and implicit learning strategies, pattern learning and apply corpus linguistics learning strategies to facilitate students’ progress in learning and using grammatical structures. On the first stage, students learn grammatical structures on the level of substitution exercises, and on later stages students apply learned structures in their own speech and writing. And as a last stage, students are trying to generate their own sentences with the studied grammatical constructions used in their own written tasks.
Keywords: Teaching grammar, syllabus, explicit and implicit instruction